Etiology, multidrug resistance, and acute-phase proteins biomarkers as in equine septic arthritis - Motta, Rodrigo Garcia [UNESP]; de Souza Araújo Martins, Lorrayne [UNESP]; da Silva, Rodrigo Costa; Portilho, Fábio Vinícius Ramos [UNESP]; Guerra, Simony Trevizan [UNESP]; da Rocha Mota, André [UNESP]; Dalanezi, Felipe Morales [UNESP]; Siqueira, Amanda Keller; de Nardi Junior, Geraldo; Listoni, Fernando José Paganini [UNESP]; Ribeiro, Márcio Garcia [UNESP] (FapUNIFESP (SciELO), 2020)
Etiology, multiple antibiotic resistance index, and acute-phase protein profile in the serum and synovial fluid of 44 horses presenting septic arthritis were investigated. Young animals up to 24 months of age not yet submitted to taming were sampled. Synovial samples from the horses were submitted to culture and bacterial isolates subjected to 18 antimicrobials to investigate the in vitro multidrug resistance pattern. Also, hematological aspects, fibrinogen, and serum levels of some acute-phase proteins (total protein, albumin, globulin, amyloid A, and C-reactive protein) were assessed. To statistical analysis, microbiological isolation were divided into four groups: G1 = animals with negative isolation, G2 = isolation of Gram-negative bacteria, G3 = isolation of Gram-positive bacteria), and G4 = isolation of fungi. Microbial isolation was obtained from 77.2% (32/44) of the synovial samples. Escherichia coli (7/44 = 15.9%), Staphylococcus aureus (5/44 = 11.4%), Streptococcus equi subsp. equi (3/44 = 6.8%), Aspergillus niger (3/44 = 6.8%), Pseudomonas aeruginosa (2/44 = 4.5%), Streptococcus equi subsp. zooepidemicus (1/44 = 2.3%), Trueperella pyogenes (1/44 = 2.3%), and Rhodococcus equi (1/44 = 2.3%) were prevalent bacterial agents. Aspergillus niger is reported by the first time as a primary agent of septic arthritis in horses. Gentamicin (84.9%), marbofloxacin (79.3%) and ceftriaxone (72.4%) were the most effective antimicrobials, whereas high resistance of the isolates (>50%) was found to erythromycin (75.9%), clarithromycin (75.9%), penicillin (69%), clindamycin (58.6%), and streptomycin (55.2%). Multiple antibiotic resistance index (≥ 0.3) was identified in 50% (16/32) of the isolates, with highest resistance in Gram-negative bacterial isolates. Serum levels of amyloid A, C-reactive protein, fibrinogen, globulin, and total protein, as well as the number of nucleated cells in the synovial fluid had values above the reference for horses, reinforcing acute-phase proteins as biomarkers in diagnosis of septic arthritis. We highlighted the diversity of microorganisms that may be involved in equine septic arthritis, the high resistance of bacterial isolates to conventional antimicrobials, the high lethality of young horses with septic arthritis, and importance of in vitro antimicrobial susceptibility pattern tests to therapeutic approaches in the disease.
Etiologia, resistência antimicrobiana e proteínas de fase aguda como biomarcadores na artrite séptica equina
Keywords: Acute-phase proteins; Etiology; Horses; Septic arthritis; Synovial fluid